Perindo Party's Political Communication Strategy in the 2024 General Election (Case Study of the People's Economy and Corruption Eradication Program) - Ondy Ondy (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2024)
The Political parties spread promises to influence society in a good or bad way before the general election. However, the communication of political party brands does not affect the image and public trust in political parties. This study analyzes and describes the Perindo Party's political communication strategy for increasing Electability in the 2024 general election. Case studies with a qualitative approach as a research method. Data collection techniques through observation, interviews, and documentation. The study results show that the political communicators of the Perindo Party have been able to convey the message of the people's economy and the eradication of corruption well; messages are expressed both verbally and nonverbally, either directly or through the media. The media used are print media, mass media, and social media, but unfortunately, they have not used traditional communicative media such as puppets in Java; non-electoral communicators provide good feedback, but electrally, they have not produced lousy feedback. Perindo experienced a